INCREASING STUDENT INTEREST AND MOTIVATION IN LEARNING WITH AUGMENTED REALITY TECHNOLOGY - Andy Rachman; Agry Alfiah; Cindy Cindhana Brilliananda (International Journal of Teaching and Learning, 2025)
Augmented reality has opened a new window in the digital learning paradigm. Its presence in the realm of education has brought about a number of impressive benefits. In many educational domains, research and development are now centered on the use of augmented reality to boost students' motivation to learn. It has been demonstrated that integrating augmented reality (AR) into the classroom improves student engagement, enriches the educational process, and raises students' interest in learning. Students can have more efficient learning experiences with AR technology, interactive, and realistic learning. For example, the development of a virus learning application using AR technology has helped students learn microorganisms such as viruses better, as well as increasing students' interest in learning in studying human blood circulation. Thus, Students' interest and drive to learn can be heightened by the use of augmented reality (AR) technology in the classroom, which can offer an engaging, dynamic, and realistic learning environment. This shows the great potential of AR technology in creating a more interesting and effective learning environment for students.